ANALISIS PINJAMAN MODAL USAHA PADA SHOPE PAYLATTER MENURUT PERSPEKTIF EKONOMI ISLAM - Neng Siska; Maulida Marpaung; Agung Prasektyo; Purnama Ramadani Silalahi (CV. Barokah Publsiher, 2022)
With the rapid development of technology, an application for online shopping (marketplace) appears. One of the biggest in Indonesia is the Shopee marketplace. Within the Shopee application there is a payment feature that can be made in installments, known as Spaylater. the author uses an analytical descriptive method to describe how the process of borrowing, payment, and settlement occurs in the event of a delay in payment on paylater practices in the shopee application. Then for data collection methods using literature review and interviews via online. The results of this study are related to the view of Islamic economics, in view of Spaylater that there are conditions from contracts that are not fulfilled in Spaylater. Because in it there is a late fine given by the Spaylater, this late fine is included in usury ignorance. Therefore the practice of spaylater is not allowed in Islam because it contains elements of usury